Effect of sub-inhibitory and inhibitory concentrations of some antibiotics and rosemary essential oil (Rosmarinus officinalis L.) on biofilm formation of Klebsiella pneumoniae (World Journal of Experimental Biosciences, 2016)
Klebsiella pneumoniae have an ability to form biofilm as one of strategies to persist and overcome host defenses. The study aims to evaluate the effectiveness of rosemary essential oil alone and in combination with some antibiotics against biofilm of K. pneumoniae isolated from urine. The antibiotics resistance pattern by disc diffusion method and minimal inhibitory concentration (MIC) of gentamicin, ciprofloxacin, amoxicillin, trimethoprim/ sulfame-thoxazole, cefotoxime and rosemary essential oil were determined. The ability to form biofilm as well as inhibition of biofilm formation of K. pneumoniae was performed. MICs 128, 0.25, 768, 64, 384 and 104 μg/ml were used. The effect of MIC and 1/2 MIC of antibiotics and rosemary essential oil that used alone and in combinations found significant differences (P ≤ 0.05) in biofilm reduction percentage of all isolates in comparison to control. In conclusion, the combination of antibiotics with rosemary essential oil effect negatively on biofilm of K. pneumoniae.